2023
DOI: 10.1039/d3py00093a
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically driven one-step triple dynamic network formation in printable tough hydrogel for self-healing tubular sensors

Abstract: Self-healing hydrogels have attracted wide attention due to their excellent biocompatibility, mechanical properties, and reparability. However, it is still a challenge to one-step construct printable self-healing tough hydrogels (PSHTHs), limiting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Our analysis of the G' and G" curves around 150 °C suggested that HOF glass resides between a high elastic state and a viscous flow state near this critical temperature point. Upon increasing the temperature to 160 °C, G' drastically decreased from ~10 6 Pa to about 10 2 Pa due to structural damage to the HOF glass 60,61 .…”
Section: Crystal Melting and Glass Formationmentioning
confidence: 99%
“…Our analysis of the G' and G" curves around 150 °C suggested that HOF glass resides between a high elastic state and a viscous flow state near this critical temperature point. Upon increasing the temperature to 160 °C, G' drastically decreased from ~10 6 Pa to about 10 2 Pa due to structural damage to the HOF glass 60,61 .…”
Section: Crystal Melting and Glass Formationmentioning
confidence: 99%